Trust in the health care professional and health outcome: A meta-analysis. - Johanna Birkhäuer; Jens Gaab; Joe Kossowsky; Sebastian Hasler; Peter Krummenacher; Christoph Werner; Heike Gerger (PLoS ONE)
Objective To examine whether patients' trust in the health care professional is associated with health outcomes. Study selection We searched 4 major electronic databases for studies that reported quantitative data on the association between trust in the health care professional and health outcome. We screened the full-texts of 400 publications and included 47 studies in our meta-analysis. Data extraction and data synthesis We conducted random effects meta-analyses and meta-regressions and calculated correlation coefficients with corresponding 95% confidence intervals. Two interdependent researchers assessed the quality of the included studies using the Strengthening the Reporting of Observational Studies in Epidemiology guidelines. Results Overall, we found a small to moderate correlation between trust and health outcomes (r = 0.24, 95% CI: 0.19-0.29). Subgroup analyses revealed a moderate correlation between trust and self-rated subjective health outcomes (r = 0.30, 0.24-0.35). Correlations between trust and objective (r = -0.02, -0.08-0.03) as well as observer-rated outcomes (r = 0.10, -0.16-0.36) were non-significant. Exploratory analyses showed a large correlation between trust and patient satisfaction and somewhat smaller correlations with health behaviours, quality of life and symptom severity. Heterogeneity was small to moderate across the analyses. Conclusions From a clinical perspective, patients reported more beneficial health behaviours, less symptoms and higher quality of life and to be more satisfied with treatment when they had higher trust in their health care professional. There was evidence for upward bias in the summarized results. Prospective studies are required to deepen our understanding of the complex interplay between trust and health outcomes.